Intervention effects and long-term changes in physical activity and cardiometabolic outcomes among children at risk of noncommunicable diseases in South Africa: a cluster-randomized controlled trial and follow-up analysis - Arnaiz, Patricia; Seelig, Harald; Gerber, Markus; Adams, Larissa; Degen, Jan; Dolley, Danielle; Joubert, Nandi; Nienaber, Madeleine; Nqweniso, Siphesihle; Steinmann, Peter; Utzinger, Jürg; du Randt, Rosa; et al. (Frontiers in Public Health, 2023)
Introduction Risk factors for noncommunicable diseases such as insufficient physical activity (PA), overweight or hypertension are becoming increasingly predominant among children globally. While school-based interventions are promising preventive strategies, evidence of their long-term effectiveness, especially among vulnerable populations, is scarce. We aim to assess the short-term effects of the physical and health KaziKidz intervention on cardiometabolic risk factors and the long-term, pre-and post-COVID-19 pandemic changes thereof in high-risk children from marginalized communities. Methods The intervention was tested in a cluster-randomized controlled trial between January and October 2019 in eight primary schools near Gqeberha, South Africa. Children with overweight, elevated blood pressure, pre-diabetes, and/or borderline dyslipidemia were identified and re-assessed 2 years post-intervention. Study outcomes included accelerometry-measured PA (MVPA), body mass index (BMI), mean arterial pressure (MAP), glucose (HbA1c), and lipid levels (TC to HDL ratio). We conducted mixed regression analyses to assess intervention effects by cardiometabolic risk profile, and Wilcoxon signed-rank tests to evaluate longitudinal changes in the high-risk subpopulation. Results We found a significant intervention effect on MVPA during school hours for physically inactive children, and among active as well as inactive girls. In contrast, the intervention lowered HbA1c and TC to HDL ratio only in children with glucose or lipid values within the norm, respectively. At follow-up, the intervention effects were not maintained in at-risk children, who showed a decline in MVPA, and an increase in BMI-for-age, MAP, HbA1c and TC to HDL ratio. Conclusion We conclude that schools are key settings in which to promote PA and improve health; however, structural changes are necessary to ensure that effective interventions reach marginalized school populations and achieve sustainable impact.